DUA MEDIA, DUA CERITA: KENAPA CNBC INDONESIA DAN BLOOMBERG TECHNOZ BERBEDA SAAT MELIPUT IHSG AMBRUK 2026 - Naufal Ilham Ramadhan; Khusnul Nuril; Fachri Juliansyah; Syaida Salwa; Devia Eka; Zainul Mukarobin; Ahmad Hakimudin Resa; Dian Setyawan; Tegar Bimantara; Malik Ibrahim (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to uncover the differences in media framing of the 2026 Indonesian Composite Stock Price Index (IHSG) crash between CNBC Indonesia and Bloomberg Technoz. Using Robert N. Entman's framing analysis model, which encompasses four dimensions (problem definition, causal interpretation, moral evaluation, and treatment recommendation), this study analyzed eight news articles published between January and April 2026. The findings reveal that CNBC Indonesia employs panic-driven framing characterized by hyperbolic and emotional diction such as